Bipolar Resistive Switching in Magnetostrictive Ni/PZT/Pt Structure for Non-Volatile Memory Applications. (1st July 2021) - Sharma, Savita; Gupta, Surbhi; Gupta, Reema; Borkar, Hitesh; Kumar, Ashok; Gupta, Vinay; Tomar, Monika
Abstract : Resistive switching (RS) has significant potential for the forthcoming generation in logical and non-volatile memory devices. Owing to their switchable spontaneous polarization ferroelectric materials can be utilized for non-volatile memory applications, e.g., FeRAM, but their destructive readout scheme limits applications. The spontaneous electrical polarization of ferroelectric materials enhances the tuning charge properties at the ferroelectric/metal interface making them appropriate for RS applications. Here, the resistive switching performance of ferroelectric Pb(Zr0.6 Ti0.4 )O3 (PZT) thin film grown on flexible Ni substrate using pulsed laser deposition were investigated. The PZT film showed both entrenched P-E ferroelectric hysteresis loop and reversible resistive switching behaviors with DC voltage sweep. Bipolar switching between a low resistance state to a high resistance state with a large ON/OFF ratio of 10 2 and resistance retention potential up to 10 10 cycles was observed. The current conduction mechanism can be understood by dual logarithm I-V curve fitting. The obtained results encourage the utilization of prepared Ni/PZT/Pt widget for the non-volatile memory applications.